Measure and test the causal relationship between the global oil market indicators for the period 1970 - 2009 using the model Hacio (Hsiao) - خالد حسين علي المرزوك; رجاء عبدالله عيسى السالم (Iraqi Journal for Administrative Sciences, 2024)
Undermine the pricing of crude oil in global markets critical risk to the general economic situation both for the countries producing or consuming countries - both developed and developing countries - and that of the strong relationship and mutual influence between the rates of economic growth and these prices, is no secret that the economic analysis in general tends to make prices (whatever these prices) independent variables affect positively or negatively on each of the quantities demanded and supplied various types of goods, respectively, that this is the IMET to the truth in absolute terms, since the required amount of a commodity or quantity before it affects an actor and a great in the formation of prices of each of them, and therefore, these amounts will be the independent variables and the impact on prices. and crude oil is of strategic goods on the one hand, and the mechanism of depletion on the other hand, must be in-depth analysis to the direction of the strongest effect, so that the two sets of producing and consuming countries have to take measures and plans and procedures that allow each of them make the most of this resource is depleted. Altaterho and strongest, is that e quantities are determined by world prices to him? The researchers used the method of analysis of elasticities, as was use of price elasticity to illustrate the impact of price in determining the size of the quantities, as used the so-called (flexibility quantity) to clarify the effect of quantities - demanded and supplied - on the formation of prices, but Achtbaralentaúj achieved has been used Oonmozj (Hacio) to measure and make sure the direction of causality in the relationship between these variables, the results were compatible with the hypothesis that Tatd research and the impact of the quantities demanded and supplied on the formation of these quantities in the global oil markets.